1999
DOI: 10.1093/protein/12.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of functional residues in the interfacial recognition domain of lecithin cholesterol acyltransferase (LCAT)

Abstract: Lecithin cholesterol acyltransferase (LCAT) is an interfacial enzyme active on both high-density (HDL) and low-density lipoproteins (LDL). Threading alignments of LCAT with lipases suggest that residues 50-74 form an interfacial recognition site and this hypothesis was tested by site-directed mutagenesis. The (delta56-68) deletion mutant had no activity on any substrate. Substitution of W61 with F, Y, L or G suggested that an aromatic residue is required for full enzymatic activity. The activity of the W61F an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…In both LPLA 2 and LCAT, the region between the cysteine residues forming the disulfide bridge in the proximity of the N-terminal region is predicted to be the most hydrophobic region that is spanned as a loop containing an amphipathic helix (8,9). The loop formed in LCAT is essential for the interaction between LCAT and lipoprotein surfaces and is thought to be indispensable for the interfacial activation of LCAT (17). By analogy, the loop in LPLA 2 may also play a crucial role in the interaction of LPLA 2 with hydrophobic structures such as phospholipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In both LPLA 2 and LCAT, the region between the cysteine residues forming the disulfide bridge in the proximity of the N-terminal region is predicted to be the most hydrophobic region that is spanned as a loop containing an amphipathic helix (8,9). The loop formed in LCAT is essential for the interaction between LCAT and lipoprotein surfaces and is thought to be indispensable for the interfacial activation of LCAT (17). By analogy, the loop in LPLA 2 may also play a crucial role in the interaction of LPLA 2 with hydrophobic structures such as phospholipid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…These lids have highly variable sequences in lipases and are able to form an amphipatic helix interacting with the lipid interface. It has been suggested that they destabilize the bilayer and facilitate both the binding of the hydrophobic substrate and its diffusion into the active site cavity of the enzyme (Peelman et al, 1999). A Trp residue in the lid is thought to bind the cleaved fatty acid in the active site of the enzyme (Martinelle et al, 1996).…”
Section: Identification Of the Arabidopsis Pdat Genementioning
confidence: 99%
“…The LCAT reaction occurs primarily on the surface of high-density lipoproteins (HDL), which contains phospholipids, cholesterol, and apolipoprotein A-I (apoA-I). Although no crystal structure exists for LCAT, the study of its structure-function relationships has been facilitated by the construction of a computer model of the catalytic core of LCAT (2)(3)(4)(5)(6). Based on its amino acid composition alone, LCAT has an intermediate hydrophobicity between integral membrane proteins and apolipoproteins (7).…”
Section: Lecithin-cholesterol Acyltransferase (Lcat)mentioning
confidence: 99%